2016
DOI: 10.1103/physreve.94.032405
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear onset of calcium wave propagation in cardiac cells

Abstract: Spontaneous calcium (Ca) waves in cardiac myocytes are known to underlie a wide range of cardiac arrhythmias. However, it is not understood which physiological parameters determine the onset of waves. In this study, we explore the relationship between Ca signaling between ion channels and the nucleation of Ca waves. In particular, we apply a master equation approach to analyze the stochastic interaction between neighboring clusters of ryanodine receptor (RyR) channels. Using this analysis, we show that signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Indeed, we find that as the SR load builds, the system's response becomes aperiodic as triggered waves begin to disrupt synchronized Ca release in the cell. In fact, previous studies have demonstrated that a nonlinear dependence of Ca release on SR load leads to dynamical instabilities such as alternans and even chaos (25,(27)(28)(29)(30). In particular, we note the classic work of Díaz et al (31), who showed that when rat ventricular cells are paced periodically with small depolarizing pulses, Ca waves occur at alternate beats, causing an alternans response at the whole cell level.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, we find that as the SR load builds, the system's response becomes aperiodic as triggered waves begin to disrupt synchronized Ca release in the cell. In fact, previous studies have demonstrated that a nonlinear dependence of Ca release on SR load leads to dynamical instabilities such as alternans and even chaos (25,(27)(28)(29)(30). In particular, we note the classic work of Díaz et al (31), who showed that when rat ventricular cells are paced periodically with small depolarizing pulses, Ca waves occur at alternate beats, causing an alternans response at the whole cell level.…”
Section: Discussionmentioning
confidence: 69%
“…This behavior resembles that of the sigmoid function model commonly used in stimulus-response models. [21,22] To further analyze this phenomenon, we employed the following sigmoid function to fit data points in Fig. 5:…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…The effect of elevated [Na + ] i has been studied in computational models, finding calcium oscillations [60], that, depending on the model, appear via a supercritical Hopf [24] or a homoclinic bifurcation [25,26]. The instability of the diastolic resting state is thus well-known [61][62][63] and it plays an important role in the initiation of various cardiac arrhythmias [22]. However, the precise PLOS COMPUTATIONAL BIOLOGY mechanistic relationship between Ca and dangerous AP repolarization is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The instability of the diastolic resting state is thus well-known [ 61 63 ] and it plays an important role in the initiation of various cardiac arrhythmias [ 22 ]. However, the precise mechanistic relationship between Ca and dangerous AP repolarization is still not well understood.…”
Section: Discussionmentioning
confidence: 99%